Lignin-zinc ion anti-freezing hydrogel electrolyte as well as preparation method and application thereof
By polymerizing ammonium acrylate in the presence of sodium lignin sulfonate and Zn(BF4)2, a lignin-zinc ion antifreeze hydrogel electrolyte was prepared, which solved the problems of time-consuming, energy-consuming and low-temperature freezing of existing hydrogel electrolytes, and achieved rapid preparation and efficient conductivity.
Patent Information
- Application Number
- CN202411839849.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing hydrogel electrolytes consume time and energy during the preparation process, and at low temperatures, the conductivity is easily reduced and the flexibility is lost due to ice.
A lignin-zinc ion antifreeze hydrogel electrolyte is prepared by polymerization of sodium lignin sulfonate (LS) and Zn(BF4)2 in the presence of sodium lignin sulfonate (LS) and Zn(BF4)2, which can be prepared quickly at room temperature and maintain high conductivity at -40°C.
It realizes the rapid preparation of hydrogel electrolytes at room temperature and maintains excellent mechanical strength and high conductivity under extremely low temperature conditions, solving the problem of freezing of hydrogels at low temperatures.
Smart Images

Figure CN119751750A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an antifreeze hydrogel electrolyte, and in particular to a lignin-zinc ion antifreeze hydrogel electrolyte, a preparation method and application thereof. Background Art
[0002] The shortage of fossil energy and increasingly severe environmental problems have stimulated the demand for green and environmentally friendly electronic energy storage devices. Due to their adjustable mechanical properties, excellent biocompatibility and high conductivity, hydrogel solid electrolytes have become a hot spot for the research of high-performance flexible electronic devices. However, the preparation process of most hydrogel electrolytes is time-consuming and energy-consuming, and requires external conditions such as ultraviolet light irradiation, special compound catalysis, or long-term heating to stimulate the initiator to produce free radicals, which greatly limits its mass production in the industrial field. Therefore, it is challenging to form hydrogels at room temperature without external stimulation.
[0003] Catechol is an important chemical raw material. Due to its strong reducing, complexing, and bioadhesive properties, some substances containing catechol have been used to prepare hydrogels with good mechanical properties and high viscosity, and have attracted widespread attention from researchers. Zong et al. constructed Cu 2+ and tannic acid (organic matter containing catechol groups) autocatalytic system, accelerating the cracking of ammonium persulfate to produce a large number of free radicals, thereby promoting the rapid polymerization of acrylic amine at ambient temperature. However, there are few attempts to use renewable natural polymers containing catechol in autocatalytic systems, which have great application prospects for green manufacturing and sustainable development. Plant-derived lignin contains aromatic natural biopolymers that are very abundant in nature, containing reduced methoxy (-OCH3) and phenolic hydroxyl (-OH) groups, which have been used as polyphenol groups to participate in the autocatalytic system of metal ions. Compared with water-soluble modified lignin and nano-sized lignin as uniformly dispersed components, sodium lignin sulfonate (LS) has good solubility in acidic environments and can be directly applied to avoid external costs, time-consuming and energy-consuming, and low yields. In addition, due to the presence of freely migrating ions in acidic water, it can not only be used for dissolution but also for conductivity, so there is a great motivation to utilize the multifunctional hydrogel of LS-metal ion catalytic system.
[0004] A large amount of free water in the hydrogel electrolyte will inevitably freeze at temperatures below 0°C, resulting in a decrease in ionic conductivity and a loss of flexibility of the hydrogel. Summary of the invention
[0005] In order to make up for the deficiencies of the prior art, the present invention provides a lignin-zinc ion antifreeze hydrogel electrolyte and a preparation method thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] In the first aspect, the present invention provides a lignin-zinc ion antifreeze hydrogel electrolyte, which is obtained by polymerization of ammonium acrylate AM in the presence of sodium lignin sulfonate-LS and Zn(BF4)2; the hydrogel electrolyte can be prepared within 5 minutes at room temperature without introducing any additional energy, the mechanical strength of the hydrogel electrolyte can reach a tensile stress of 0.14MPa under a strain of 1750%, and the alkali metal ions make the hydrogel electrolyte have a tensile strength of 3.67mScm at -40°C. -1 Ultra-high extreme low temperature conductivity.
[0008] In a second aspect, the present invention provides a method for preparing a lignin-zinc ion antifreeze hydrogel electrolyte, and the preparation method is as follows:
[0009] (1) First, HCl was dissolved in deionized water to prepare a 1 M aqueous solution;
[0010] (2) Then, Zn(BF4)2 was dissolved in an acidic solution to prepare Zn(BF4)2 acidic solutions with different concentrations of 0-5M, and AM was continuously added;
[0011] (3) Dissolve LS with different mass ratios in HCl acid solution, add N, N-methylenebisacrylamide MBA, and stir in an ice bath for 1 hour;
[0012] (4) Add 0.03 g of initiator APS, followed by stirring in an ice bath; inject the prepared precursor solution into a mold and seal it at room temperature for polymerization.
[0013] Preferably, in step (2), the amount of AM added is 3 g.
[0014] Preferably, in step (3), the mass ratio of LS is one of 0wt%, 0.1wt%, 0.3wt%, and 0.5wt%.
[0015] Preferably, in step (3), the amount of HCl acid solution is 5.0 ml and the amount of MBA added is 1 mg.
[0016] Preferably, in step (4), the amount of initiator APS added is equivalent to 1 wt% of the monomer mass.
[0017] Preferably, in step (4), the stirring time is 30 s.
[0018] In a third aspect, the present invention provides an application of a lignin-zinc ion antifreeze hydrogel electrolyte in the preparation of a sensor for detecting a strain sensing signal, a temperature sensing signal, or one of various motions.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. A simple, general and rapid gel method based on sodium lignin sulfonate and zinc ions is proposed. The complex formed by catechol and alkali metal ions promotes the balance of redox reaction. The generated SO4 - ·, OH· and singlet oxygen ( 1 O2) free radicals are responsible for the rapid polymerization of vinyl monomers. Alkali metal ions play a dual role in the rapid polymerization and antifreeze properties of the hydrogel electrolyte. By adjusting the mass ratio DL and the metal ion concentration, the gelation time can be adjusted by changing the mass ratio of lignin and the concentration of zinc ions or acids. The hydrogel electrolyte can be prepared within 5 min at room temperature without introducing any additional energy. The mechanical strength of the hydrogel electrolyte can reach a tensile stress of 0.14 MPa at a strain of 1750%. Alkali metal ions give the hydrogel electrolyte a tensile strength of 3.67 mS cm at -40 °C. -1 The ultra-high extreme low temperature conductivity of the hydrogel electrolyte sensor can detect various parts of the human body in a wide temperature range and output a stable resistance signal. This work provides a lignin-zinc ion autocatalytic method for the rapid preparation of multifunctional hydrogels.
[0021] 2. The sensor constructed with this hydrogel electrolyte has excellent electrochemical properties at both room temperature and low temperature, effectively filling the application gap of low-temperature sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described below in conjunction with the accompanying drawings.
[0023] Figure 1 Schematic diagram of the rapid initiation of multifunctional hydrogel polymerization by the self-catalytic system;
[0024] Figure 2 Actual image of rapid polymerization: (a) infrared thermal imaging; (b) polyAM-LS 0.1 -Zn4 polymerization physical picture; (c) polyAM polymerization physical picture;
[0025] Figure 3 To study the mechanism of rapid polymerization: gelation time under different contents / concentrations of (a) LS, (b) HCl and (c) Zn(BF4)2; XPS spectra of C1s of (d) LS and (e) LS-HCl-Zn(BF4)2; (f) electron paramagnetic energy spectrum;
[0026] Figure 4 LS-Zn 2+ Mechanism diagram of the autocatalytic system;
[0027] Figure 5Mechanical properties of hydrogels: (a) Mechanical properties at different LS contents; (b) Maximum stress-strain at different LS contents; (c) Elastic modulus and toughness at different LS contents; (d) Mechanical properties at different Zn(BF4)2 contents; (e) Maximum stress-strain at different Zn(BF4)2 contents; (f) Elastic modulus and toughness at different Zn(BF4)2 contents
[0028] Figure 6 polyAM-LS 0.3 -Zn4 hydrogel physical picture
[0029] Figure 7 For PolyAM and polyAM-LS 0.3 - Actual picture of Zn4 hydrogel at room temperature and -40℃;
[0030] Figure 8 Study on the antifreeze performance of hydrogel electrolyte: (a) polyAM-LS 0.3 -Zn y DSC of hydrogel electrolyte; (b) polyAM-LS 0.3 -Zn y Ionic conductivity of hydrogel at different temperatures; (c) polyAM-LS 0.3 -Zn y Temperature dependence of hydrogel ionic conductivity;
[0031] Fig. 9 Performance study of the hydrogel sensor: (a) change of relative resistance under different strains; (b) response time and recovery time of the sensor; (c) change of relative resistance over time when the sensor is cyclically stretched under tensile strain; (d) change of resistance of the sensor at different temperatures; (e) schematic diagram of the monitored sensing position; (f) change of relative resistance over time when the finger is cyclically stretched at -20°C; change of relative resistance over time when (g) the finger, (h) elbow and (i) knee are cyclically stretched at room temperature. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with the accompanying drawings.
[0033] Example 1
[0034] Materials and reagents
[0035] Table 1 Main raw materials and reagents
[0036]
[0037] Experimental instruments and equipment
[0038] Table 2 Main experimental instruments and equipment
[0039]
[0040] Experimental sample preparation
[0041] Antifreeze zwitterion polyAM-LS x -Zn y Preparation of electrolyte
[0042] PolyAM-LS was obtained by polymerization of AM in the presence of sodium lignin sulfonate LS and Zn(BF4)2. x -Zn y Hydrogel electrolyte. First, HCl was dissolved in deionized water to prepare a 1M aqueous solution. Zn(BF4)2 was then dissolved in an acidic solution to prepare acidic solutions of Zn(BF4)2 of different concentrations from 0 to 5M, and 3gAM was continued to be added. LS of different mass ratios (0wt%, 0.1wt%, 0.3wt%, 0.5wt%) were then dissolved in 5.0ml LiCl acidic solution, 1mg MBA was added, and stirred in an ice bath for 1 hour. 0.03g initiator APS (equivalent to 1wt% of the monomer mass) was added, followed by stirring in an ice bath for 30s. The precursor solution was injected into the mold and sealed at room temperature for a few minutes for polymerization.
[0043] Example 2 Test Characterization
[0044] Characterization of rapid gelation
[0045] The polymerization time was calculated from the time after the addition of APS (0s). When the temperature reached the maximum, the polymerization reaction was completed. The LS and LS-Zn 2+ X-ray photoelectron spectroscopy (XPS) of the autocatalytic system determined the DL-Zn 2+ The oxidation degree of the autocatalytic system was recorded on an ESR spectrometer (Bruker EMXnano). 2+ 5,5-Dimethyl-1-pyrroline-orthooxide (DMPO) spin-trapping electron spin resonance (ESR) spectroscopy of an autocatalytic system to determine sulfuric acid and hydroxyl radicals as well as singlet oxygen.
[0046] Mechanical properties test
[0047] The mechanical properties were tested using a universal mechanical tester (Hensgrand, WDW-02, Jinan). The tensile sample was a cuboid with a length of 50 mm, a width of 7 mm, a thickness of 3 mm, and a strain rate of 50 mm min -1 .
[0048] Measurement of electrical conductivity of hydrogel electrolytes
[0049] The ionic conductivity (σ) of the hydrogel electrolyte was measured by electrochemical impedance spectroscopy (EIS) in a CHI660E electrochemical workstation. First, the hydrogel electrolyte was filled in a CR927 battery case, and the battery case containing the electrolyte was stabilized at different temperatures for 2 to 4 hours. The impedance was then measured at the corresponding temperature. It is best to measure each sample three times to reduce errors. Ionic conductivity (σ, mS cm -1 ) is calculated by the following formula.
[0050]
[0051] Where, L is the thickness of the sample to be tested (cm), R is the resistance (Ω), and S is the contact area of the electrolyte (cm 2 ).
[0052] Characteristic test
[0053] Differential scanning calorimetry (DSC) was tested using a TA2500 instrument. The sample was first cooled from 40 °C to -80 °C, and then heated from -80 °C to 40 °C. The cooling and heating rates were both 5 °C min -1 , the sample mass is between 8-10 mg. The samples are tested under nitrogen protection.
[0054] Electrochemical performance test of the sensor
[0055] The electrochemical signal of the hydrogel was recorded on the CHI660E workstation by measuring the impedance-time curve of the hydrogel electrolyte impedance over time. The strain coefficient is the strain sensitivity of the hydrogel sensor, and the calculation formula is as follows:
[0056]
[0057] The corresponding changes in resistance are measured, R0 and R are the initial resistance and real-time resistance, respectively. ε is the strain.
[0058] Example 3
[0059] Results and Discussion
[0060] Rapid polymerization mechanism
[0061] The present invention uses acrylamide (AM) monomer for the hydrogel polymerization of the system, and verifies the synergistic autocatalytic effect of lignin and zinc ions. In the system, sodium lignin sulfonate (LS) and Zn(BF4)2 are used to form an autocatalytic system. In order to make LS play a better catalytic role, hydrochloric acid ( Figure 1 ).
[0062] The multifunctional hydrogel finally prepared is abbreviated as polyAM-LS x -Zn y , where x is the mass fraction of LS and y is the molar concentration of Zn(BF4)2 in the system. 2+ It is the decisive factor for the rapid polymerization of AM monomers. The various components in the precursor solution work synergistically to achieve the rapid preparation of multifunctional hydrogel electrolytes within 5 minutes. As observed by infrared thermal imaging ( Figure 2 a), after APS, LS and Zn(BF4)2 were added to the precursor solution, the solution began to release heat at 3 minutes at ambient temperature of 20-25°C, reached the heat peak at 5 minutes, and then gradually began to cool down, indicating that the hydrogel reaction polymerization was basically completed within 5 minutes. Figure 2 As shown in b, compared with the precursor solution containing LS and Zn(BF4)2, which can form a gel in 5 min, the precursor solution without LS and Zn(BF4)2 cannot form a gel ( Figure 2 c). These experimental results confirm that LS and Zn(BF4)2 can promote the rapid gelation of the precursor solution at ambient temperature, which is largely convenient for large-scale preparation.
[0063] In addition, the present invention shows through further experimental data that the gelation rate of the hydrogel is positively correlated with the content of LS and the concentration of HCl / Zn(BF4)2. Figure 3 As shown in a, when the precursor solution is controlled at 1M HCl and 4M Zn(BF4)2, when the LS content increases from 0 to 0.1wt%, the gelation time decreases from 3 hours to 8 minutes. With the further increase of LS content, the gelation time will gradually shorten to 3min. The increase of acid concentration in the system also significantly promotes the gelation time. When the HCl concentration changes from 0M to 0.5M, the gelation time can be shortened from 11.5min to 6min ( Figure 3 b). In addition, by increasing the Zn(BF4)2 concentration from 0 to 4 M, the gelation time of the hydrogel can be reduced from 24 min to 5 min ( Figure 3 c). The experimental results show that increasing the content / concentration of LS, HCl and Zn(BF4)2 is conducive to rapid gelation, and the lack of any component cannot reduce the gelation time to less than 10 min. Therefore, this shows that the LS-Zn system is a method that can achieve rapid polymerization, in which the catechol groups obtained after LS acid hydrolysis can promote the monomer to form a Zn 2+ Rapid polymerization was achieved in the presence of
[0064] In the system of the present invention, the mechanism for triggering rapid polymerization is completely different from the rapid polymerization mechanism of the redox system formed by high-valent oxidized metal ions and lignin reported in the literature. 2+ X-ray photoelectron spectroscopy (XPS) analysis and electron spin resonance (ESR) spectroscopy were carried out to investigate the mechanism of rapid polymerization of the 2-Hydroxy-2-nitropropene and 2-amino-2-nitropropene. Figure 3 The XPS spectrum in c shows that DL has a high CO / C-OH peak at 286.3 eV and a low C=O peak at 288.9 eV. When LS is treated with HCl and Zn(BF4)2, the area of the CO / C-OH-peak increases and the area of the C=O peak decreases significantly ( Figure 3 e), indicating that the -OH and -OCH3 groups of LS are hydrolyzed by acid to form catechol structures. In the system of the present invention, the methoxyl groups of lignin are hydrolyzed under acidic conditions to form catechol of lignin, and these catechol salts are easily oxidized by S2O8 of APS. 2- Oxidized to quinone groups of lignin. At the same time, APS is reduced to produce sulfate radicals (SO4 - ·), sulfate radicals can interact with water molecules (H2O) to produce hydroxyl radicals (OH·), and four signals with relative intensities of 1:2:2:1 confirm the existence of OH· ( Figure 3 f). It should be noted that the present invention also detects a typical three-line EPR spectrum with the same intensity ( Figure 3 f), the spectrum was assigned to singlet oxygen ( 1 O2) Therefore, OH· and 1 O2 is believed to contribute to the rapid polymerization of monomers. In general, the present invention proposes that under acidic conditions, sodium lignin sulfonate is more likely to generate easily oxidized catechol groups. It is worth noting that zinc ions and the catechol groups of lignin can form a stable complex, which can effectively improve the reversibility of the redox reaction between catechol and quinone. This zinc ion-catechol complex is more unstable than the zinc salt of catechol, thereby promoting the reduction of the quinone group of lignin ( Figure 4 ). In addition, acidic environment and Zn 2+ The synergistic effect makes it easier for the autocatalytic system to produce more free radicals. 2+ In an acidic environment, rapid gelation can be achieved within 5 minutes.
[0065] Mechanical properties of hydrogel electrolytes
[0066] Excellent mechanical properties are crucial for the application of hydrogel electrolytes. Therefore, polyAM-LS was evaluated by a series of tensile and rheological tests. x -Zn yMechanical properties of hydrogel electrolytes. After adding sodium lignin sulfonate (LS), the tensile strain of the hydrogel did not increase significantly at 0.1wt%. Gradually increasing the content of LS, the tensile strain value increased significantly, indicating that LS as a component in the gel has a certain effect on the tensile strain ( Figure 5 a) For the ultimate tensile strength, the sample without DL has a significant decrease after adding LS, which indicates that the addition of LS destroys the original hydrogel structure, resulting in a sharp drop in strain. Figure 5 As shown in b, the maximum stress intensity is 0.25MPa without LS, and gradually decreases to 0.11MPa with the increase of LS content. The ultimate tensile strain is 1750% without LS, and gradually increases to 2200% with the increase of LS content. This shows that the increase of LS will destroy the mechanical strength of the hydrogel and make the hydrogel easier to stretch. Figure 5 As shown in Figure c, the elastic modulus is 32.8 kPa when LS is not present. As the LS content increases, the elastic modulus decreases to 13.8 kPa. The toughness is also 201.28 kJ m when LS is not present. -3 However, the toughness will decrease first and then increase with the increase of LS, reaching the minimum value of 107.5KJ m -3 Later increased to 130.68KJ m -3 .
[0067] The effect of Zn(BF4)2 concentration on the mechanical properties of polyAM hydrogels was also studied. After adding LiCl, the tensile strength and strain of the hydrogels were weakened, indicating that the addition of Zn(BF4)2 would seriously affect the mechanical properties of PolyAM hydrogels. As for the tensile strength, as the concentration of Zn(BF4)2 increased, the ultimate tensile strength increased from 0.242±0.01MPa at 0M to 0.057±0.01MPa at 5M ( Figure 5 d). Similarly, with the addition of Zn(BF4)2, the tensile strain decreases from 1929% to 1169% ( Figure 5 d). Figure 4 As shown in the figure, the maximum stress intensity is 0.242MPa when there is no Zn(BF4)2. As the concentration of Zn(BF4)2 increases, the maximum stress gradually decreases to 0.057MPa. The ultimate tensile strain is 1929% when there is no Zn(BF4)2. As the concentration of Zn(BF4)2 increases, it gradually decreases to 1169%. This shows that the increase of Zn(BF4)2 will destroy the mechanical properties of the hydrogel. Figure 4As shown in the figure, the elastic modulus is 42.4 kPa when Zn(BF4)2 is not present. As the concentration of Zn(BF4)2 increases, the elastic modulus gradually decreases to 12.45 kPa. The toughness value is also 258.7 kJ m when Zn(BF4)2 is not present. -3 As the concentration of Zn(BF4)2 increases, the toughness gradually decreases to 33KJ m -3 .like Figure 6 Representative example shown, polyAM-LS 0.3 -Zn4 hydrogel electrolyte is flexible enough to withstand various types of deformation, such as load-bearing, twisting, and knotting. It is worth noting that the polyAM-LS weighing 1.2g 0.3 -Zn4 hydrogel electrolyte can successfully lift 200g, which is 167 times its own weight, indicating that the hydrogel has excellent mechanical carrying capacity.
[0068] Antifreeze properties and electrical conductivity of hydrogel electrolytes
[0069] The essence of water freezing is the phase transition from disordered water to ordered water driven by hydrogen bonds. Researchers generally add high concentrations of salt, ionic liquids, organic solvents, antifreeze proteins, etc. to water solvents. These methods all achieve the antifreeze effect by destroying the hydrogen bond network between water molecules. In the case of the present invention, the addition of Zn(BF4)2 can not only accelerate the polymerization of hydrogels, but also give hydrogels antifreeze properties and high conductivity. Figure 7 As shown, after freezing at -30 °C for 4 h, polyAM hydrogels lost their flexibility. 0.3 -Zn4 hydrogels retain a certain flexibility and can be stretched to five times their initial state.
[0070] Differential scanning calorimetry (DSC) is also used to measure the effect of LiCl concentration on the freezing point of the electrolyte. Figure 8 As shown in a, when the concentration of Zn(BF4)2 is 0, 2, 4 and 5M, the freezing points of the electrolyte are -6.2, -19.7, -27.2 and -35.6℃ respectively. It is worth noting that when the concentration of LiCl is 5M, there is only an exothermic peak at -35.6℃ on the DSC curve, indicating that there is no heat flow in the temperature range of -35 to 40℃. In addition to the above antifreeze performance, the conductivity of electrolytes with different Zn(BF4)2 concentrations at different temperatures was also measured. Figure 8 b, polyAM-LS 0.3 -Zn0 exhibits poor low temperature conductivity. In contrast, polyAM-LS 0.3 -Zn4 and polyAM-LS 0.3-Zn5 has good ionic conductivity between -40℃ and 25℃. At 25℃, the conductivity can reach 40.07mS cm -1 and 45.2 mS cm -1 Even at -40°C, polyAM-LS 0.3 -Zn4 and polyAM-LS 0.3 -Zn5 can also achieve a conductivity of 3.67mS cm -1 and 3.9 mS cm -1 It is well known that the relationship between the ionic conductivity of an electrolyte and the inverse of the absolute temperature is always linear and follows the Arrhenius law ( Figure 8 c). The lower the activation energy (Ea), the more favorable the ion migration. polyAM-LS 0.3 -Zn5 electrolyte has the lowest Ea of 12.05 eV, which is consistent with the ionic conductivity data.
[0071] Electrical sensing characteristics of the sensor
[0072] Considering the above properties, polyAM-LS 0.3 The Zn4 hydrogel electrolyte can be rapidly polymerized (gelation at room temperature for 5 min) and exhibits strong mechanical properties (stress: 0.14 MPa, strain: ~1760%) and low-temperature conductivity (3.67 mS cm at -40 °C). -1 ), which is superior to the hydrogel electrolytes reported in the literature. 0.3 -Zn4 hydrogel electrolyte has a practical application value. It is also prepared into a sensor for detecting strain sensing signals and temperature sensing signals. In addition, the hydrogel electrolyte also has the characteristics of high sensitivity and fast response. With the increase of strain (ε), for ε≤400% and 400%<ε≤900%, the strain coefficients are 0.01 and 0.013 ( Fig. 9 a). In addition, the response time and recovery time of the sensor made of hydrogel ( Fig. 9 b) 4s and 5s respectively, indicating that polyAM-LS 0.3 -Zn4 hydrogel sensors can sensitively detect various movements. Fig. 9 As shown in c, no obvious signal fluctuation was observed in the tensile strain range of 100% to 600%, which proves that the designed sensor has stable signal output capability. 0.3 -Zn4 hydrogel electrolyte has excellent antifreeze performance, and the present invention can also be applied to temperature sensors that change according to different temperatures. Fig. 9As shown in Figure d, the sensor still has the ability to output stable signals at <0℃ and can be used normally at -30℃. 0.3 -Zn4 hydrogel sensors attached to various parts of the human body to detect human motion ( Fig. 9 e). Fig. 9 As shown in Figures 9f and 9g, the sensor can be mounted on the finger to obtain stable signal fluctuations at -20 and 25°C, respectively, which shows that the hydrogel sensor can normally monitor different movements of the human body at low temperatures. In addition to the fingers, the resistance changes of the bending at the elbow and knee are also monitored. It is easy to detect the resistance signals in different states, indicating that the hydrogel sensor can be attached to various parts of the human body to detect related activities of the human body.
[0073] In summary, the invention has discovered a method of using a lignin macromolecule-zinc ion autocatalytic system (DL-Zn 2+ ) is a simple method for preparing hydrogels with good antifreeze properties and high electrical conductivity in a short time. Specifically, the catechol groups generated by the hydrolysis of sodium lignin sulfonate (LS) in an acidic environment are more easily oxidized to quinones, which can be oxidized by Zn 2+ Complexation leads to the formation of catechol, thereby establishing the redox balance between catechol and quinone and promoting the conversion of APS into SO4 - · then reacts with water to generate OH·. This autocatalytic system can also generate singlet oxygen free radicals ( 1 O2), and multiple free radicals jointly initiate the polymerization of ammonium acrylate (AM) monomers to form a gel. The newly developed hydrogel has an environmentally friendly and fast polymerization method, excellent conductivity, strong mechanical properties, and antifreeze. Therefore, this work will provide new ideas for the design of multifunctional hydrogel solid electrolytes for flexible electronic devices and make it possible to mass-produce hydrogels.
Claims
1. A lignin-zinc ion antifreeze hydrogel electrolyte, characterized in that: The hydrogel electrolyte is obtained by polymerization of ammonium acrylate AM in the presence of sodium lignin sulfonate -LS and Zn(BF4)2; the hydrogel electrolyte can be prepared within 5 minutes at room temperature without introducing any additional energy, and the mechanical strength of the hydrogel electrolyte can reach 0.14MPa tensile stress under 1750% strain, and the alkali metal ions make the hydrogel electrolyte have 3.67mS cm at -40℃. -1 Ultra-high extreme low temperature conductivity.
2. A method for preparing the lignin-zinc ion antifreeze hydrogel electrolyte according to claim 1, characterized in that: The preparation method is as follows: (1) First, HCl was dissolved in deionized water to prepare a 1 M aqueous solution; (2) Then, Zn(BF4)2 was dissolved in an acidic solution to prepare Zn(BF4)2 acidic solutions with different concentrations of 0-5M, and AM was continuously added; (3) Dissolve LS in different mass ratios in HCl acid solution, add N, N-methylenebisacrylamide MBA, and stir in an ice bath for 1 hour; (4) Add 0.03 g of initiator APS, followed by stirring in an ice bath; inject the precursor solution into a mold and seal it at room temperature for polymerization.
3. The method according to claim 2, characterized in that In step (2), the amount of AM added is 3 g.
4. The method according to claim 2, characterized in that: In step (3), the mass ratio of LS is one of 0wt%, 0.1wt%, 0.3wt%, and 0.5wt%.
5. The method according to claim 2, characterized in that: In step (3), the amount of HCl acid solution is 5.0 ml and the amount of MBA added is 1 mg.
6. The method according to claim 2, characterized in that In step (4), the amount of initiator APS added is equivalent to 1 wt% of the monomer mass.
7. The lignin-zinc ion antifreeze hydrogel electrolyte according to claim 2, characterized in that: In step (4), the stirring time is 30 s.
8. An application of the lignin-zinc ion antifreeze hydrogel electrolyte according to claim 1 in preparing a sensor for detecting one of a strain sensing signal, a temperature sensing signal, and various motions.
Citation Information
Patent Citations
Flexible zinc-air battery gel electrolyte as well as preparation method and application thereof
CN112563627A
Preparation method and application of lignin-polypyrrole conductive hydrogel material
CN117777494A
Preparation method and application of lignin-alkali metal ion autocatalysis system rapid gelation anti-freezing hydrogel electrolyte
CN118256006A
Reusable Hydrogels for Removing a Heavy Metal Ion and Uses Thereof
KR1020160057111A